Production of biofuel via co-cracking of rice waste and sewage sludge / Fairous Salleh - Salleh, Fairous (2011)
Economic development and rising standards of living in Malaysia have led to increase in the quantity of waste generation. It is estimated that over 9 million tonnes of rice waste are generated annually from rice milling industry. The total production of domestic sewage sludge in Malaysia is 3.2 million cubic meter per year. Normally rice wastes are used as animal feed, composting, burned as thermal energy for drying purposes and the others are burned on the field. Generally, most of the sewage sludge waste was disposed by sanitary landfills, agriculture decomposition, incineration and dumping into the sea. The utilization of the two sources of waste via energy recovery has the potential to solve waste management problem and also generate useful energy. Pyrolysis is one of the thermochemical process which can convert biomass into energy.